Repeatability of lung function tests during methacholine challenge in wheezy infants. Issue 11 (1st November 1998) - Delacourt, Christophe; Benoist, Marie-Rose; Waernessyckle, Serge; Rufin, Patrick; Brouard, Jean-Jacques; de Blic, Jacques; Scheinmann, Pierre
Abstract : BACKGROUND: The repeatability of lung function tests and methacholine inhalation tests was evaluated in recurrently wheezy infants over a one month period using the rapid thoracic compression technique. METHODS: Eighty one wheezy, symptom free infants had pairs of methacholine challenge tests performed one month apart. Maximal flow at functional residual capacity (V˙maxfrc ) and transcutaneous oxygen tension (Ptco 2 ) were measured at baseline and after methacholine inhalation. Provocative doses of methacholine causing a 15% fall in Ptco 2 (PD15 Ptco 2 ) or a 30% fall inV˙maxfrc (PD30 V˙maxfrc ) were determined. RESULTS: Large changes in V˙maxfrc were measured from T1 to T2 with a mean difference between measurements (T2 —T1 ) of 7 (113) ml/s and a 95% range for a single determination forV˙maxfrc of 160 ml/s. The mean (SD) difference between pairs of PD30 V˙maxfrc measurements was 0.33 (1.89) doubling doses with a 95% range for a single determination of 2.7 doubling doses. Repeatability of PD15 Ptco 2 was similar. A change of 3.7 doubling doses of methacholine measured on successive occasions represents a significant change. CONCLUSIONS: Baseline V˙maxfrc values are highly variable in wheezy, symptom free infants. Using either V˙maxfrc or Ptco 2 as the outcome measure for methacholine challenges provided similar repeatability. A change of more than 3.7 doubling doses of methacholine is required for clinical significance.